PELATIHAN GURU BERWIBAWA UNTUK MENINGKATKAN KOMPETENSI SOSIAL DALAM MENGAJAR GURU PADA SMP â€œXâ€ - Mira Dudona; Sumedi P Nugraha; Uly Gusniarti (State Islamic University (UIN) Ar-Raniry, 2016)
This study aims to measure the improvement of the teacherâ€™s social competence in teaching junior high school in